Approximate stock valuation of Grupo Nutresa S.A. (2020)
The aim of this document is to propose an Approximate Stock Valuation of Grupo Nutresa SA., supported by the Discounted Cash Flow method in which the present value of future cash flows is determined by discounting them at a rate that reflects the cost of contributed capital (WACC). Throughout the document, an exhaustive analysis is made of the food and beverage industry, and also of the company, to have an overview of the company that is being valued. Finally, a sensitivity analysis is carried out that reveals the most relevant variables in the financial model.